The properties of petroleum fluids - McCain, William D., 1933- (Tulsa, Okla. : PennWell Books, 1990)
This book is a reference on petroleum fluids. It details the physical properties most often used to describe petroleum liquids and gases. It includes chapters on phase behavior, equations of state, reservoir fluids, dry gases, wet gases, surface separation, equilibrium-ratio correlations and gas hydrates. Chapters devoted to properties of black oils provide definitions, field data, reservoir fluid studies and correlations. Example problems are used to promote understanding and exercises covering all concepts are given at the end of each chapter.
A conveniently arranged petroleum fluids reference book covering components, properties, and equations for the various fluids and gases. Contents: Introduction and scope Water-in-crude-oil emulsions Characterization, phase behavior, and field processing of crude oil Separation of gas, oil and water Dehydration and desalting of crude oil Crude sweetening and stabilization Pumps Measurement of crude oil Fire heaters Pipeline transportation Energy conservation Instrumentation and process control Pressure relief and flaring Case histories Appendices.
Includes bibliographical references and index.
Keywords: Petroleum; Natural gas; Oil reservoir engineering